Millers church history ; v. 1 short papers on church history from the Apostolic age to the twentieth century, written from a scriptural standpoint - Miller, Andrew, 1810-1883 (London, UK Pickering and Inglis)
Contents : v. 1 : A.D. 32 to A.D. 1106 : The First Thousand Years : From the founding of the Church to the death of King Henry I. Includes bibiographical references.
Brethren writer. Originally written pre-1878.
Keywords: Church history; Brethren movement -- history and philosophy